2015
DOI: 10.1016/j.febslet.2015.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal‐stem‐cell‐derived exosomes accelerate skeletal muscle regeneration

Abstract: a b s t r a c tMesenchymal stem cell (MSC) transplantation is used for treatment of many diseases. The paracrine role of MSCs in tissue regeneration is attracting particular attention. We investigate the role of MSC exosomes in skeletal muscle regeneration. MSC exosomes promote myogenesis and angiogenesis in vitro, and muscle regeneration in an in vivo model of muscle injury. Although MSC exosomes had low concentrations of muscle-repair-related cytokines, a number of repair-related miRNAs were identified. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
349
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 443 publications
(367 citation statements)
references
References 31 publications
14
349
2
2
Order By: Relevance
“…CM contains high levels of angiogenic factors such as VEGF and IL-6 and enhances bone ingrowth and fracture healing by stimulating endothelial cells [47]. However, as we previously reported, although VEGF and IL-6 levels in MSC exosomes are low compared with CM and CM-Exo, MSC exosomes induce angiogenesis to a greater extent [36]. These results suggest that the acceleration of fracture healing by MSC exosomes is not solely attributable to MCP-1, -3, SDF-1, and angiogenic factors.…”
Section: /2mentioning
confidence: 68%
See 2 more Smart Citations
“…CM contains high levels of angiogenic factors such as VEGF and IL-6 and enhances bone ingrowth and fracture healing by stimulating endothelial cells [47]. However, as we previously reported, although VEGF and IL-6 levels in MSC exosomes are low compared with CM and CM-Exo, MSC exosomes induce angiogenesis to a greater extent [36]. These results suggest that the acceleration of fracture healing by MSC exosomes is not solely attributable to MCP-1, -3, SDF-1, and angiogenic factors.…”
Section: /2mentioning
confidence: 68%
“…system. We previously described the top 20 most highly expressed miRNAs in MSC exosomes and CM-Exo [36]. The top 30 most highly expressed miRNAs in MSC and HOS exosomes were very similar (Table 1).…”
Section: Cytokines and Micrornas In Msc Exosomesmentioning
confidence: 71%
See 1 more Smart Citation
“…In the cardiovascular system, exosomes have been suggested as cardioprotective agents (Lai et al, 2010); they have been shown to have proangiogenic effects (Bian et al, 2014) and involvement in reduction of apoptosis and cardiac fibrosis (Feng et al, 2014). Arslan et al (2013) showed that a single intravenous administration of exosomes was effective in enhancing cardiac function and geometry after myocardial infarction due to bioenergetics re-establishment (increased ATP production), oxidative stress reduction and prosurvival signaling activation (enhanced PI3K/Akt signaling) (Arslan et al, 2013 (Nakamura et al, 2015). In the nervous system, MSC derived exosomes have been evaluated in the treatment of neurological and neurodegenerative diseases; they have been shown to enhance angiogenesis and neurogenesis, reduce inflammation and improve spatial learning and sensorimotor function (Kim et al, 2016;Zhang et al, 2015).…”
Section: Hematopoietic Stem Cell Based Drugsmentioning
confidence: 99%
“…6 MSC-derived exosomes (MSC-Ex), membrane-enclosed vesicles found in MSC-conditioned medium (MSC-CM), have been reported to contribute to angiogenesis, neurite outgrowth, and skeletal muscle regeneration. [7][8][9] We previously demonstrated that hucMSCs and hucMSC-Ex could alleviate liver fibrosis, promote liver and renal injury repair, and improve wound healing. [10][11][12] hucMSC-Ex may have similar protective and reparative properties as their cellular counterparts in tissue repair.…”
Section: Introductionmentioning
confidence: 99%